Whitney - Macdonald, Kevin, 1967-; Houston, Whitney; Brown, Bobby, (Vocalist); Brown, Bobbi Kristina; Houston, Cissy (Santa Monica, CA : Lionsgate, 2018)
Whitney Houston is a musical icon, known for such hit songs as "How Will I Know," "I Will Always Love You" and "I Wanna Dance with Somebody (Who Loves Me)." Her debut album, "Whitney Houston," set industry records as the best-selling debut album for a female singer. The documentary follows her life and career, culminating in her untimely death at the age of 48. Her friends and family describe their relationship with the singer and her private struggles.
"Made in association with the Estate of Whitney E. Houston"--Container.
Originally released as a documentary film in 2018.
Wide screen (1.78:1).
Special features: Audio commentary with producer & director; Motion photo gallery featuring images courtesy of The Estate of Whitney E. Houston.
Film editor, Sam Rice-Edwards.
Whitney Houston, Bobby Brown, Bobbi Kristina Brown, Cissy Houston.
Keywords: Houston, Whitney; Singers -- United States -- Biography; African American women singers -- United States -- Biography; Biographical films; Documentary films